International financial reporting standards and earning management: Comparative study of pre-post full convergence of IRRS in Malaysia - Kwong, Wing Chong Garrett; Mohamad, Shafi; Shafie, Rohami; Sadiq, Muhammad (Advance Scientific Research, 2020)
Purpose – The purpose of this study is to examine the influence of full convergence of IFRS (International Financial Reporting Standards) on earnings management using a sample of companies listed on Bursa Malaysia given that the rationale for adoption of IFRS in Malaysia was to make the published financial statements of public listed companies more transparent and comparable. Design/Methodology/Approach – A sample of 200 firms listed on Bursa Malaysia (Malaysian Stock Exchange) were chosen to investigate and examine the quality of accounting information by evaluating and measuring the Earning Management in the context of Malaysian listed companies. This research was carried out using the earnings management model, which was first introduced by Jones (1991) and later modified by Dechow et al. (1995). Findings – The findings from this research suggested that the full convergence of IFRS is negatively and significantly associated with earnings management. Research Limitations/Implications – This study examined only one aspect of IFRS i.e. full convergence of IFRS on the intensity of Earnings Management, hence any conclusions drawn are based on that one aspect only. Furthermore, EM (Earnings management) is not limited to and identified via the accruals model only, so future studies may use other models as well. Finally, the residuals of accruals model was extracted cross-sectionally, which assume that all firms in the industry tend to employ similar accruals techniques. In practice however, firms differ from one another in structure, character and in many other regards.